Loop-Mediated Isothermal Amplification for Detecting Four Major Foodborne Pathogens in Meat and Meat Products - Xin Li; Mingxue Zhu; Siyuan Wang; Weijia Li; Baohong Ren; Lingbo Qu; Xiaoling Zhang (Foods)
Listeria monocytogenes, Staphylococcus aureus, Salmonella enterica, and Escherichia coli O157:H7 are four major foodborne pathogenic bacteria found in meat and meat products, which pose significant threats to human health. In this study, we developed specific loop-mediated isothermal amplification (LAMP) primers targeting these four pathogenic bacteria. Following the optimization of system components and reaction parameters, four rapid and simplified LAMP-based detection assays were established, which enabled the visual detection of these four pathogenic bacteria within 40–50 min. The three established LAMP assays targeting L. monocytogenes, S. aureus, and E. coli O157:H7 achieved species-level discrimination, whereas the LAMP method for Salmonella exhibited genus-level specificity. The detection limits of the LAMP assays were determined as follows: 1.8 × 101 colony forming units (CFU)/mL for L. monocytogenes, 5.1 × 101 CFU/mL for S. aureus, 1.2 × 101 CFU/mL for S. enterica, and 3.3 × 103 CFU/mL for E. coli O157:H7, with sensitivity improved by 10–1000-fold compared to conventional PCR. The developed LAMP assays were used to analyze 52 meat and meat product samples, and 7 samples were positive, which was consistent with the results of the conventional PCR and culture-based methods, demonstrating an accuracy rate of 100% for the LAMP methods. In conclusion, the established LAMP assays exhibit high specificity, enhanced sensitivity, and result visualization, making them suitable for on-site rapid detection in food safety monitoring.